Assessing the feasibility and acceptability of online measurements of exhaled volatile organic compounds (VOCs) in children with preschool wheeze: a pilot study - Tim Coats; Matthew Richardson; Michael Wilde; Erol A Gaillard; Misty Makinde; Karl Holden; Paul Monks (BMJ Publishing Group, 2021)
Background Investigating airway inflammation and pathology in wheezy preschool children is both technically and ethically challenging. Identifying and validating non-invasive tests would be a huge clinical advance. Real-time analysis of exhaled volatile organic compounds (VOCs) in adults is established, however, the feasibility of this non-invasive method in young children remains undetermined.Aim To determine the feasibility and acceptability of obtaining breath samples from preschool children by means of real-time mass spectrometry analysis of exhaled VOCs.Methods Breath samples from preschool children were collected and analysed in real time by proton transfer reaction-time of flight-mass spectrometry (PTR-TOF-MS) capturing unique breath profiles. Acetone (mass channel m/z 59) was used as a reference profile to investigate the breath cycle in more detail. Dynamic time warping (DTW) was used to compare VOC profiles from adult breath to those we obtained in preschool children.Results 16 children were recruited in the study, of which eight had acute doctor-diagnosed wheeze (mean (range) age 3.2 (1.9-4.5) years) and eight had no history of wheezing (age 3.3 (2.2-4.1) years). Fully analysable samples were obtained in 11 (68%). DTW was used to ascertain the distance between the time series of mass channel m/z 59 (acetone) and the other 193 channels. Commonality of 12 channels (15, 31, 33, 41, 43, 51, 53, 55, 57, 60, 63 and 77) was established between adult and preschool child samples despite differences in the breathing patterns.Conclusion Real-time measurement of exhaled VOCs by means of PTR-MS is feasible and acceptable in preschool children. Commonality in VOC profiles was found between adult and preschool children.